Characterization of SrO samples produced at two different temperatures - Ince, Turan; Ateş, Tankut; Bulut, Niyazi; Keser, Serhat; Kaygili, Omer (Niyazi BULUT, 2021)
In this study, two strontium oxide (SrO) samples were produced at two different temperatures of 950 °C and 1000 °C, and the characterization of these samples was carried out using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). The as-obtained results were compared with both each other and the available data in the literature, and all the as-observed results were reported in more detail. It was found that the temperature of the heat treatment affected significantly the crystallite size and morphology and SrO samples can be easily prepared in high purity via a wet chemical method as a facile route.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik